1985
DOI: 10.1111/j.2044-8309.1985.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

The rules of social relationships

Abstract: Rules also extend to relationships. Certain formal and legal relationship rules already exist, Studies of organizations have shown that two principles operate for a system to Harrk (1974) made a distinction between constitutive rules, which define what is Personal Relationships. London/Beverly Hills: Sage. rules. International Journal of P.sychology.Requests for reprints should be addressed to Michael Argyle, Department of Experimental Psychology. University of Oxford. South Parks Road, Oxford OX1 3UD. UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
81
0
8

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 1 publication
2
81
0
8
Order By: Relevance
“…One link between the cultural level of beliefs, values and anxieties and the domestic level of daily practices can be found in the symbolic, social and practical negotiation of parenting (and corresponding child-related) rules and roles. Argyle and Henderson (1985) stress that a rule is a culturally shared, prescriptive expectation regarding the correct way of acting, this in turn resting on a shared belief about the importance of such action. Relationships are, therefore, normative; they instantiate and reproduce cultural values.…”
Section: Regulating the Media Regulating The Familymentioning
confidence: 99%
“…One link between the cultural level of beliefs, values and anxieties and the domestic level of daily practices can be found in the symbolic, social and practical negotiation of parenting (and corresponding child-related) rules and roles. Argyle and Henderson (1985) stress that a rule is a culturally shared, prescriptive expectation regarding the correct way of acting, this in turn resting on a shared belief about the importance of such action. Relationships are, therefore, normative; they instantiate and reproduce cultural values.…”
Section: Regulating the Media Regulating The Familymentioning
confidence: 99%
“…Whilst family and friendship relations are likely to endorse similar 5 relationship rules (see Argyle et al, 1985), they represent different relational contexts and as 6 such they are likely to be governed by distinct rules reflecting the specific goals or functions 7 of such relationships (Argyle & Henderson, 1985a). In contrast to the friendship relations 8…”
mentioning
confidence: 99%
“…Moreover, our findings corroborate the notion that rules in 20 relationships are situational-specific (see e.g., Baxter et al, 2001), coaches and athletes' 21 leadership may vary depending on whether interactions take place in training versus 22 competition. 23 Argyle and his colleagues (Argyle et al, 1985; found that 24 rules within the context of task-focused relationships (e.g., doctor-patient, superior-25 subordinate) contained low endorsement of reward-rules (i.e., rules that provide an exchange 26…”
mentioning
confidence: 99%
See 2 more Smart Citations